Pengaruh Campuran Air Kelapa dan Daun Gamal sebagai Pupuk Cair terhadap Pertumbuhan Vegetatif Tomat (Solanum lycopersicum L.) - N. Putri Sumaryani; Ni Nyoman Parmithi; I Wayan Beny Gunawan (Emasains : Jurnal Edukasi Matematika dan Sains, 2018)
Tomato is one type of fruit plant with high Vitamin C and antioxidant content. Efforts that can be used to increase the vegetative growth of tomato plants is by using organic fertilizer. One of the organic fertilizers that can be used is coconut water and gamal leaves. This study aims to determine the effect of coconut water mixture and gamal leaf as liquid fertilizer to the vegetative growth of tomato plants (Solanum lycopersicum L.).This research is classified as an experimental research using Completely Randomized Design. The population in this research is 400 tomato plants. The sample in this research is tomato plant with the amount of 300 plants taken by Simple Random Sampling technique, and become four replications. Each treatment consisted of: 1) treatment without liquid fertilizer (P0), 2) liquid fertilizer from coconut water mixture and gamal leaf with volume 40 ml / l (P1), 3) liquid fertilizer from coconut water mixture and gamal leaf with a volume of 80 ml / l (P2); 4) liquid fertilizer from a mixture of coconut water and gamal leaves with volume of 120 ml / l (P3); and 5) liquid fertilizer from coconut water mixture and gamal leaf with volume 160 ml / P4). The data obtained in this study were analyzed using one wa Analysis of Varian (ANOVA) using SPSS for Windows 16.0. The result of data analysis shows that there is influence of coconut water mixture and gamal leaf as liquid fertilizer to vegetative growth of tomato plant (Solanum lycopersicum L.). The best treatment for vegetative growth of tomato plants (Solanum lycopersicum L.) with volume 160 ml / l (P4).